Inhibition of PRC2 histone methyltransferase activity increases TRAIL‐mediated apoptosis sensitivity in human colon cancer cells. Issue 4 (20th December 2012) - Benoit, Yannick D.; Laursen, Kristian B.; Witherspoon, Mavee S.; Lipkin, Steven M.; Gudas, Lorraine J.
Abstract Colorectal cancer is ranked among the top leading causes of cancer death in industrialized populations. Polycomb group proteins, including Suz12 and Ezh2, are epigenetic regulatory proteins that act as transcriptional repressors of many differentiation‐associated genes and are overexpressed in a large subset of colorectal cancers. Retinoic acid (RA) acts as a negative regulator of PcG actions in stem cells, but has shown limited therapeutic potential in some solid tumors, including colorectal cancer, in part because of retinoic acid receptor β silencing. Through treatment with RA, Suz12 shRNA knockdown, or Ezh2 pharmacological inhibition with 3‐deazaneplanocin A (DZNep), we increased TRAIL‐mediated apoptosis in human colorectal cancer cell lines. This increased apoptosis in human colon cancer cells after RA or DZNep treatment was associated with a ∼2.5‐fold increase in TNFRSF10B (DR5) transcript levels and a 42% reduction in the H3K27me3 epigenetic mark at the TNFRSF10B promoter after DZNep addition. Taken together, our findings indicate that pharmacological inhibition of Polycomb repressive complex 2 histone methyltransferase activity may constitute a new epigenetic therapeutic strategy to overcome RA non‐responsiveness in a subset of colorectal tumors by increasing TRAIL‐mediated apoptosis sensitivity. J. Cell. Physiol. 228: 764–772, 2013. © 2012 Wiley Periodicals, Inc.